Personality factors and Intercollegiate Tennis Association ranking - Kovacs, M. (The Journal of Strength and Conditioning Research, 2010)
In tennis players, personality characteristics may be an important component to determine success. To examine the influence personality plays in collegiate male tennis players. 93 active NCAA Division I collegiate tennis players participated in this study which involved the International Personality Item Pool (IPIP) 50 item questionnaire focused on the big-five personality characteristics. These five personality characteristics are extraversion, agreeableness, conscientiousness, openness and emotional stability. Nine demographic questions were also administered looking at sleeping habits, collegiate grade point average (GPA), handedness collegiate singles and doubles ranking. Bivariate correlations were used to analyze personality and tennis ranking in collegiate tennis players. A One-way (3X2) ANOVA was used to analyze differences between high, low and non-ranked collegiate tennis players for each of the big five personality traits (high and low). A high correlation was found between singles and doubles rankings (.82), and a moderate correlation between GPA and hours of sleep (.44). The personality characteristics showed low and moderate correlations with Intercollegiate Tennis Association (ITA) rankings. Tennis players who are high in conscientiousness had higher Intercollegiate Tennis Association singles rankings F (1,91) = 9.58, p<.05. Tennis players who were high in emotional stability had higher ITA singles rankings F (1,91) = 15.18, p<.05. Follow up odds ratios were examined to determine likelihoods, with higher rankings predicted approximately a three times higher likelihood of also having high ratings of conscientiousness and emotional stability. This information is important as it may increase the interest in the relationship between personality and tennis performance and could become beneficial as tool to use during the athlete recruiting process.